Language Style and Register Used by Famous Content Creators in Tiktok Application - Ida Lisdawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The phenomenon of social media today has a tremendous impact on young people's social life and Indonesian language usage. Content creators contribute to the change because they introduce the words as their trademark to get their viewers’ attention quickly, followed by young people who have unlimited access to social media. This study aims to provide an overview of the new vocabulary introduced by content creators and analyse the language style they use when performing. The subject of this study uses two well-known TikTok content creators who have the most viewers according to a survey given randomly to 26 young people at a university in Bandung, West Java. Methods used in data collection were observing, writing and concluding and descriptive. The results of data processing are presented in the descriptive technique. The result showed that the TikTok content creator mostly used the uncommon word that could be classified as a register that added viewer vocabulary so that the vocabulary in society has undergone significant changes and additions. Its changes can negatively impact if there are no limits on the use of vocabulary and social media. One solution that can do is to strengthen the character of the younger generation to maintain their identity as young Indonesians amid the widespread influence of social media.